Cusp and Nightside Auroral Sources of O+ in the Plasma Sheet. Issue 12 (9th December 2019) - Kistler, L. M.; Mouikis, C. G.; Asamura, K.; Yokota, S.; Kasahara, S.; Miyoshi, Y.; Keika, K.; Matsuoka, A.; Shinohara, I.; Hori, T.; Kitamura, N.; Petrinec, S. M.; et al.
Abstract: Energetic O + outflow is observed from both the dayside cusp and the nightside aurora, but the relative importance of these regions in populating the plasma sheet and ring current is not known. During a storm on 16 July 2017, the Arase and MMS satellites were located in the near‐earth and midtail plasma sheet boundary layers (PSBL). During the storm main phase, Arase and MMS both observe O + in the lobe entering the PSBL, followed by a time period with energy‐dispersed bursts of tailward‐streaming O + . The ions at MMS are at higher energies than at Arase. Trajectory modeling shows that the ions coming in from the lobe are cusp origin, while the more energetic bursty ions are from the nightside aurora. The observed and simulated energies and temporal dispersion are consistent with these sources. Thus, both regions directly contribute O + to the plasma sheet during this storm main phase. Plain Language Summary: The magnetosphere is the region of space encompassed by Earth's magnetic field. The plasma trapped in the magnetosphere can come both from the Sun and from the ionosphere, the ionized layer of the atmosphere. The ionospheric contribution to the plasma increases during geomagnetic storms. These ions get energized in the auroral oval and flow out along magnetic field lines. During storms, this outflow can contain a large fraction of O + . There are two particular regions where this O + outflow occurs, one on the dayside and one on the nightside. This study looks at the contribution of O + from these two regions. Two spacecraft in different locations in the magnetosphere during the storm were able to observe the signatures of ions from both regions indicating that both regions are important during the peak of the storm. Key Points: Arase and MMS are fortuitously located in the near‐Earth and midtail plasma sheet boundary layer during the main phase of a storm Both spacecraft observe O + from both the nightside aurora and the cusp, with higher energies observed at greater distances The energy differences and timing of the O + at the two spacecraft are consistent with modeled transport